KOLABORASI MODEL STAD dan PETA (Untuk Meningkatkan Aktivitas dan Hasil Belajar) - Siti Halimatus Sakdiyah; Oktavianus Salomon (IKIP PGRI Jember, 2018)
Applying STAD and Map Learning is expected to increase student activity and learning outcomes. The stages of STAD learning model is divided into material presentation stage, group learning stage, quiz stage and award stage. This research uses qualitative approach with Classroom Action Research (PTK) which consist of 2 cycles. Each cycle consists of planning, execution, observation and reflection. The subjects of this study were students of class IV SDN Kebonsari 1 Malang. Based on the observation of student activity cycle I is 77.23% with enough category, and increased in cycle II to 87.72%, with good category. This shows that there is an increase of 10.49%. While the average value of the test cycle I is 75.45 with the percentage of completeness of student learning outcomes of 89.06%, and increased in the test cycle II with an average score of 79.15 with the percentage of students' learning completeness of 95.31%. Which is an increase in cycle II of 6.25% of cycle I. Based on the above data obtained the conclusion that STAD and map learning can improve student activities and learning outcomes on the material Distribution of flora and fauna.